Strategy to Overcome Barriers to Implementing Electronic Medical Records in Inpatient Care at Mandor Health Center, West Kalimantan - Clara, Apriana; Rachman, Arif; Rubini, Rizki Adriansyah (ProBisnis : Jurnal Manajemen, 2025)
Community Health Centers (Puskesmas) function as the main provider of public health services while encouraging community participation. As an institution that handles a large amount of data, Puskesmas requires an accurate and efficient data management system to support structured reporting. The purpose of this study was to analyze strategies in overcoming obstacles in the implementation of medical records in inpatient services at the Mandor Puskesmas. This study was conducted at the Mandor Puskesmas, located in Landak Regency, West Kalimantan Province. This study used a qualitative approach with an instrumental case study method. In this study, the researcher involved five main subjects who had important roles in the implementation of Electronic Medical Records in the inpatient unit of the Mandor Puskesmas. The data analysis process consisted of several stages, namely data reduction, data presentation, and drawing conclusions. Based on the results of the study, there were several factors that hindered the implementation of Electronic Medical Records (EMR) in Inpatient Services at the Mandor Puskesmas, West Kalimantan. These factors includeMan; Machine; Method; Material;as well asMoney. Some of the proposed strategies are the addition of medical and IT personnel who have competence in the field of RMIK and health information technology, routine training for medical personnel, improving the quality of internet networks and server maintenance, procuring new computers that meet specifications, and preparing clear and detailed SOPs regarding the implementation of RME.